Pengaruh Moral Sensitivity, Whistleblowing System, Kompetensi Aparatur dan Budaya Organisasi terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa di Kecamatan Sojol - Dhiza Salsabila; Munipa Munipa; Muhammad Syafaat; Dewi Salmita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The management of village funds in Indonesia is a crucial issue due to the high potential for fraud at the village level, despite the fact that the funds distributed each year continue to increase. In Sojol Subdistrict, Donggala Regency, cases of corruption involving village officials show that even though regulations have been established, practices in the field are still prone to irregularities that directly impact the welfare of the village community. This study aims to examine the influence of moral sensitivity, whistleblowing systems, official competence, and organizational culture on fraud prevention in village fund management. This study uses a quantitative approach, with data collected through a questionnaire distributed to 54 respondents consisting of village officials and members of the Village Council (BPD). The results of this study indicate that moral sensitivity, whistleblowing systems, official competence, and organizational culture simultaneously have a significant impact on fraud prevention in village fund management, although the level of influence of each varies. This underscores the importance of moral integrity and reporting systems, as well as strengthening competence and organizational culture at the village level.